2017
DOI: 10.1007/s10021-017-0171-7
|View full text |Cite
|
Sign up to set email alerts
|

Productivity and Temperature as Drivers of Seasonal and Spatial Variations of Dissolved Methane in the Southern Bight of the North Sea

Abstract: Dissolved CH 4 concentrations in the Belgian coastal zone (North Sea) ranged between 670 nmol l-1 nearshore and 4 nmol l-1 offshore. Spatial variations of CH 4 were related to sediment organic matter (OM) content and gassy sediments. In nearshore stations with fine sand or muddy sediments, the CH 4 seasonal cycle followed water temperature, suggesting methanogenesis control by temperature in these OM-rich sediments. In offshore stations with permeable sediments, the CH 4 seasonal cycle showed a yearly peak fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 83 publications
5
56
0
Order By: Relevance
“…Thus, the emission rates reported in this study are net emissions, which represent a balance between production and consumption of the whole system. In wetlands, a clear positive correlation between emission of methane and net ecosystem production has been documented (Borges et al, ; Bridgham et al, ; Whiting & Chanton, ; Yvon‐Durocher et al ). It has also been shown that the methane production in the rhizosphere of wetland and tundra plants is to a large extent driven by recent plant photosynthates in the form of root exudates (Dorodnikov et al, ; King & Reeburgh, ; Megonigal et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the emission rates reported in this study are net emissions, which represent a balance between production and consumption of the whole system. In wetlands, a clear positive correlation between emission of methane and net ecosystem production has been documented (Borges et al, ; Bridgham et al, ; Whiting & Chanton, ; Yvon‐Durocher et al ). It has also been shown that the methane production in the rhizosphere of wetland and tundra plants is to a large extent driven by recent plant photosynthates in the form of root exudates (Dorodnikov et al, ; King & Reeburgh, ; Megonigal et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the photosynthetically derived oxygen that is transported to the rhizosphere by the roots of wetland plants (i.e., radial oxygen loss) can also suppress methane production (Laanbroek, 2009), and in temperate seagrasses, such a release of oxygen to the rhizosphere has been shown to also protect against sulfides and other toxins (Brodersen et al, 2015Pedersen et al, 1998). Methanogenesis is also a temperature-dependent process (Dunfield et al, 1993;Sanz-Lázaro et al, 2011;Van Bodegom & Stams, 1999;Westermann, Ahring, & Mah, 1989;Zeikus & Winfrey, 1976), and rapid changes in temperature can result in simultaneous changes in methane production (Borges et al, 2018;Chin, Lukow, & Conrad, 1999;Høj, Olsen, & Torsvik, 2008;Segers, 1998;Van Bodegom & Stams, 1999). This is partly due to a direct effect on the process, where the methane production can have a Q 10 (i.e., a relative increase in activity after an increase in temperature of 10°C) of 1.3-28 (Dunfield et al, 1993;Segers, 1998;Van Hulzen, Segers, Bodegom, & Leffelaar, 1999) and partly because of a temperature-driven shift in the composition and activity of the microbial community (Conrad, Klose, & Noll, 2009;Høj et al, 2008;Pender et al, 2004).…”
Section: Relative Importance Of Temperature and Etr On Methane Emismentioning
confidence: 99%
“…In a recent study, Borges et al (2018) suggested a close coupling between eutrophication of the Belgian coastal zone and methane emissions from sediments. These authors compared methane concentrations 26 years apart and found a significant decrease in water column CH 4 concentrations, which they attribute to oligotrophication of the coastal zone during that time period.…”
Section: Outlook and Implicationsmentioning
confidence: 99%
“…No overall pattern of controlling factors of methane emission were revealed by Ortiz-Llorente and Alvarez-Cobelas (2012); thus, the authors concluded that local studies are vital for assessing methane emission and its controlling factors. The presence and strength of a pycnocline is especially critical in the control of methane emission, as this emission is much stronger from environments without stratification (Borges et al, 2017) than from stratified systems where MOX can consume part of the methane . Temperature is another important environmental control factor, as methane production is very temperature sensitive (i.e.…”
Section: Diffusive Methane Fluxmentioning
confidence: 99%
“…methanogenesis is higher at higher temperatures). Consequently, tropical and temperate regions would be expected to show higher methane concentrations and emissions (Borges et al, 2017;Lofton et al, 2014), while polar regions would have lower concentrations and emissions. However, as methane oxidation is only somewhat influenced by temperature, this may offset methane consumption vs. methane production in polar areas (Lofton et al, 2014), thereby resulting in lower methane concentrations overall in polar regions.…”
Section: Diffusive Methane Fluxmentioning
confidence: 99%